Comparing long wavelength and short wavelength vertical-cavity surface-emitting lasers - Yap D.F.W.; Leow Y.H.; Koh S.P.; Tiong S.K. (2023)
In this paper, analysis of long wavelength and short wavelength VCSELs are presented. From the simulation results, power output and turn on delay (TOD) are investigated with the variation of Dext (distance between laser facet and fibre). In addition, different Rox (oxide aperture radius) were tested to investigate the effect of the Rox on the modulation transfer function. In the simulation, the comparison with and without carrier noise, photon noise and phase noise from external cavity among long wavelength and short wavelength of VCSELs are carried out. However, thermal effects, longitudinal transport in quantum wells (QWs) and electrical parasitic will not be taken into account in this study. 2008 IEEE.